2013
DOI: 10.1271/bbb.120740
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Production of γ-Aminobutyric Acid in Soybeans Using High Hydrostatic Pressure and Precursor Feeding

Abstract: The effects were investigated of the glutamic acid (Glu) substrate concentration on the generation and kinetics of γ-aminobutyric acid (GABA) in soybeans treated under high hydrostatic pressure (HHP; 200 MPa for 10 min at 25 °C). The conversion of Glu to GABA decreased with increasing initial Glu concentration in the soybeans. The crude glutamate decarboxylase (GAD) obtained from the HHP-treated soybeans showed substrate inhibition. The GABA production rate in the HHP-treated soybeans fitted the following subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…The amount of glutathione (GSH) was determined as described (Ueno et al . ), and the concentration was calculated against commercially available standard of GSH. The glutamic acid decarboxylase (GAD) activity was determined according to Ueno et al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of glutathione (GSH) was determined as described (Ueno et al . ), and the concentration was calculated against commercially available standard of GSH. The glutamic acid decarboxylase (GAD) activity was determined according to Ueno et al .…”
Section: Methodsmentioning
confidence: 99%
“…The glutamic acid decarboxylase (GAD) activity was determined according to Ueno et al . (), with γ‐aminobutyric acid (GABA) as standard. One unit of GAD activity was defined as the production of 1 µmol GABA per hour.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-pressure-induced damages to cellular structure were also elucidated in a separate study on the relative drying rate (RDR) of Japanese radish samples before and after HHP pretreatment; the RDR was found to be similar to that after chloroform vapor treatment but lower than that in the case of heat treatment and freeze-thaw pretreatment [ 7 ]. HHP on legumes such as green bean [ 8 , 9 ] chickpea [ 10 ], cowpea [ 11 ], and soybean [ 12 , 13 ] had been reported from the viewpoints of structural, physical or biochemical changes. However, in another study, Eshtiaghi et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is speculated that the HPP of 600 Mpa treatment may cause severe damage to those enzymes that convert glutamate to related metabolites, so there is a higher amount of glutamate accumulation. Ueno et al [ 52 ] evaluated the effects of treatment of soybeans at 200 MPa for 10 min at 25 °C on L-glutamate concentration, GABA production, and their kinetics. Their results showed that the conversion of L-glutamate to GABA decreased with increasing initial L-glutamate concentration in soybeans.…”
Section: Resultsmentioning
confidence: 99%